Treatment patterns and clinical outcomes for patients with melanoma and central nervous system metastases: A real‐world study. (7th December 2021) - Tawbi, Hussein; To, Tu My; Bartley, Karen; Sadetsky, Natalia; Burton, Elizabeth; Haydu, Lauren; McKenna, Edward
Abstract: Background: Patients with melanoma and central nervous system (CNS) metastases have poor survival outcomes. We investigated real‐world treatment patterns and overall survival (OS) of patients with melanoma and CNS metastases. Methods: A retrospective analysis utilizing a nationwide de‐identified electronic health record‐derived database was undertaken in patients diagnosed with advanced melanoma between January 2011 and September 2018. Patients with any visit ≤90 days of metastatic diagnosis and with confirmed CNS metastases were included. Results: Of 3473 patients diagnosed with advanced melanoma, 791 patients with confirmed CNS metastases were identified and included in this analysis. Synchronous CNS metastasis (≤30 days of metastatic diagnosis) was associated with longer median OS than metachronous CNS metastasis (>30 days after metastatic diagnosis, 0.58 vs 0.42 years). Stereotactic radiosurgery (SRS) was the most common treatment (40.5%) alone or in combination with other local or systemic therapies, being more frequent in patients diagnosed in 2015+ versus 2011–2014 (44.1% vs 35.5%, respectively). The most common systemic treatment was immune checkpoint inhibitors (ICIs; 30.5%), predominantly anti‐cytotoxic T‐lymphocyte antigen 4 (CTLA‐4) alone (2011–2014) and anti‐programmed death‐1 alone or in combination with anti–CTLA‐4 (2015+). Median OS was longest in SRS‐treated patients (1.17 years) regardless of number of CNS metastases. Median OS for SRS‐treated patients increased from 0.83 years (2011–2014) to 1.75 years (2015+). In multivariable analysis, the effect of SRS remained significant after adjustment for sex, race, intracranial and extracranial disease burden, and timing of CNS metastases. Interaction testing to examine potential synergy between SRS/whole‐brain radiation therapy and ICIs found no significant interaction. Conclusions: Despite advances in treatment, patients with melanoma and CNS metastases have poor survival outcomes. Prevalence of SRS increased over time and was associated with improved outcomes. Abstract : This retrospective analysis of real‐world data demonstrated that patients with melanoma and CNS metastases have poor survival outcomes despite recent advances in treatment options. Prevalence of stereotactic radiosurgery increased over time and was associated with improved outcomes.